Implementation of a Project-Based Learning (PjBL) STEM Approach in IPAS Learning to Improve Students’ Scientific Literacy and Critical Thinking Skills - Yudiana, I Kadek Edi; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Universitas Pendidikan Ganesha, 2025)
The Industrial Revolution 4.0 brings significant changes in human life with automation and access to information technology, which requires mastery of 4C skills: Critical Thinking, Creative Thinking, Communication, and Collaboration. Critical thinking skills are very important in supporting problem solving and decision making, and are closely related to scientific literacy. However, PISA data shows that the scientific literacy of Indonesian students is still low, with an average score of 74.56 in science learning. To improve this quality, the Merdeka Curriculum is implemented with a focus on project-based learning (PjBL), but the results are not optimal. The STEM-based PjBL model, which integrates science, technology, engineering, and mathematics, has proven effective in improving scientific literacy and critical thinking skills. This study used the Classroom Action Research (CAR) method with two cycles. The pre-cycle results showed an average value of scientific literacy of 73.28 and critical thinking of 72.14, below the Minimum Completion Criteria (KKM). Cycle I with PjBL increased the average value to 79.42 for scientific literacy and 79.28 for critical thinking. In Cycle II, after improvements to the teaching modules and learning media, the average value increased further to 82.28 and 82, indicating the success of the implementation of STEM-based PjBL. This model encourages problem solving, critical thinking, and collaboration, and prepares students with essential skills in the digital era.